Full-scale research on heat transfer and pressure drop of high flux plate heat exchanger. (25th May 2017) - Hu, Zhuohuan; He, Xie; Ye, Li; Yang, Mo; Qin, Guihua
Highlights: A full-scale simulation model of double chevron PHE with high flux was proposed. To validate the numerical simulations, an experimental apparatus was built. The experimental campaign was based on principle of equal Reynolds number method. The Realizable k-ε model is found to give closest results to experimental data. Abstract: Efficiency of Plate Heat Exchanger (PHE) is extremely influenced by flowing condition and heat transfer, which depend on PHE's geometrical characteristics. In this work, a full-scale simulation model was built to research heat transfer and pressure drop of double chevron PHE with high flux. And experiment apparatus based on the principle of equal Reynolds number method has also been established to validate the numerical simulations and select out the best turbulence model for full-scale simulation. Compared with experimental results, the average error of Realizable k-ε model was less than 6%, which means the Realizable k-ε model can reveal the heat transfer and flow characteristics of PHE with high flux most accurately.